2017
DOI: 10.1128/iai.00866-16
|View full text |Cite
|
Sign up to set email alerts
|

The Rhomboid Protease GlpG Promotes the Persistence of Extraintestinal Pathogenic Escherichia coli within the Gut

Abstract: Extraintestinal pathogenic Escherichia coli (ExPEC) strains are typically benign within the mammalian gut but can disperse to extraintestinal sites to cause diseases like urinary tract infections and sepsis. As occupation of the intestinal tract is often a prerequisite for ExPEC-mediated pathogenesis, we set out to understand how ExPEC colonizes this niche. A screen using transposon sequencing (Tn-seq) was performed to search for genes within ExPEC isolate F11 that are important for growth in intestinal mucus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Similarly, the main model rhomboid protease GlpG of Escherichia coli , widely distributed in Gram‐negative bacteria, is extremely well‐characterised structurally and mechanistically (Strisovsky et al , ; Baker & Urban, ; Zoll et al , ), yet its biological function is unknown. A recent report proposed a role of GlpG in the survival of a pathogenic strain of E. coli in the mouse gut (Russell et al , ), but the mechanism has not been demonstrated and it is not clear how specific the phenotype is, because rescue experiment has not been reported. Current knowledge of functions of rhomboid proteases in Gram‐positives is similarly sketchy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the main model rhomboid protease GlpG of Escherichia coli , widely distributed in Gram‐negative bacteria, is extremely well‐characterised structurally and mechanistically (Strisovsky et al , ; Baker & Urban, ; Zoll et al , ), yet its biological function is unknown. A recent report proposed a role of GlpG in the survival of a pathogenic strain of E. coli in the mouse gut (Russell et al , ), but the mechanism has not been demonstrated and it is not clear how specific the phenotype is, because rescue experiment has not been reported. Current knowledge of functions of rhomboid proteases in Gram‐positives is similarly sketchy.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, deletion of a closely related plasmid from the neonatal meningitis E. coli isolate RS218 attenuates bacterial virulence during systemic infections in rat pups (65). In addition, a number of pUTI89-associated genes have been linked with ExPEC mucus and glucose metabolism in vitro (30). To determine if pUTI89 facilitates gut colonization by F11, an F11 derivative that was cured of the plasmid was tested in our mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…Mice were housed 3–5 per cage, and were allowed to eat (irradiated Teklad Global Soy Protein-Free Extruded chow) and drink antibiotic-free water ad libitum . Competitive indices (CIs) were calculated as the ratio of mutant over WT bacteria recovered in the feces divided by the ratio of mutant over WT bacteria in the inoculum, as noted previously (30).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, for FdnH and FdoH, we only observed further degradation following exposure to copper stress (Fig E and F). Therefore, it may be that the in vivo colonisation defect exhibited by E. coli lacking GlpG results from its failure to deal with accumulated components of respiratory complexes in the membrane (Russell et al , ). Furthermore, efforts to determine the mechanisms of rhomboid catalysis have been hampered by the lack of rhomboid substrate pairs for enzymatic and structural studies.…”
Section: Discussionmentioning
confidence: 99%
“…TatA processing by AarA is critical for the function of the Tat system, which mediates quorum sensing in P. stuartii (Stevenson et al , ). Despite current knowledge of GlpG structure and activity, the only phenotypes identified for E. coli glpG mutants are an enhanced resistance to cefotaxime (Clemmer et al , ) and reduced intestinal colonisation in a murine model (Russell et al , ). However, the molecular mechanisms underlying these phenotypes are unknown.…”
Section: Introductionmentioning
confidence: 99%